Kartagener’s syndrome: unusual dental morphology - S. J. MERRETT & P. DURNING (Paediatric Dentistry, 2005)
Kartagener’s syndrome (KS) is described as a triad of situs inversus (mirror image organ placement),bronchiectasis and sinusitis [1–3].